Peningkatan Aktivitas dan Prestasi Belajar Penjumlahan Menggunakan Alat Peraga Realia pada Siswa Kelas 2 SD Negeri 3 Gedong Tataan Kabupaten Pesawaran TP 2019/2020 - Siti Maryana (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
Based on pre-study activities and student achievement of SD Negeri 3 Gedong Tataan, Pesawaran Regency in learning Mathematics is low. The purpose of this research is to increase the activity and learning achievement of Addition Using Realia teaching aids in grade 2 students of SD Negeri 3 Gedong Tataan Pesawaran for the 2019/2020 academic year. The research method uses CAR through the research cycle, data is obtained from tests to obtain achievement data and observation sheets to observe student learning activities and is also supported by observations by observers. The results of the research on learning activities in the first cycle an average of 68.5%, the second cycle an average of 86.5%, the third cycle an average of 99.5% (cycle I to cycle II increased 18%, cycle II to cycle III increased 13 %, student activity increased by an average of 15.5%.The average learning achievement (complete) Cycle I was 22 (completed 73%), Cycle II averaged 25 (completed 83%), Cycle III averaged 30 ( completed 100%). That is, from cycle I to Cycle II increased 10%, Cycle II to cycle III increased 13%, or student learning outcomes increased by an average of 11.5%. Thus, the use of realia teaching aids can increase activity and Learning achievement Summing for Grade 2 students of SD Negeri 3 Gedong Tataan Pesawaran Regency for the 2019/2020 academic year.